1677PDA phase II study of pazopanib as front-line therapy in patients with non-resectable or metastatic soft tissue sarcomas who are not candidates for chemotherapy. (1st October 2019) - Hirbe, A; Luo, J; Seetharam, M; Toeniskoetter, J; Kershner, T; Agulnik, M; Varun, M; Milhem, M; Parkes, A; Robinson, S; Okuno, S; Attia, S; et al.
Abstract: Background: Anthracycline based chemotherapy remains the standard of care for first-line treatment for advanced and metastatic soft tissue sarcoma. In some instances, patients may not be a candidate for chemotherapy based on age or other comorbidities leaving no viable treatment option. Pazopanib is a multi-targeted tyrosine kinase inhibitor that is FDA approved as a second-line and beyond treatment for metastatic soft tissue sarcoma. We proposed a phase II study to evaluate pazopanib as a first-line agent in patients with non-resectable or metastatic disease who are not candidates for cytotoxic chemotherapy. Methods: Eligible patients were at least 18 years old, not a candidate for chemotherapy, and had not received prior systemic therapy for sarcoma. Initial starting dose of pazopanib was 200mg BID titrated to 800mg daily. The primary endpoint was clinical benefit rate (CBR) (CR + PR + SD per RECIST 1.1) at 16 weeks. The sample size of 56 evaluable patients was calculated to provide 80% power to test a hypothesized CBR of ≥ 35% against an unfavorable CBR of ≤ 20%. If ≥ 17 patients achieved benefit, the null CBR of 20% would be rejected would be rejected at a nominal 5% alpha level (actual alpha=0.043). Secondary endpoints included PFS rate, OS, quality of life, and serum biomarkers. Results: 56 patients are included in the intention-to-treat analysis. Currently 52 patients are evaluable for CBR. Data from the final 4 patients will be added at the time of presentation. Median PFS was 12 (8.29∼24.14) weeks and PFS rate at 16 weeks was 40% (CI 0.2893-0.5617). Median OS was 8.6 months, CBR=36.5% (19/52), 95% CI = 0.2362∼0.5104, 2-sided exact binomial test p = 0.00507. No new or unexpected adverse events were seen. The most common Grade I-II adverse events were diarrhea, nausea, and anemia. The most common grade III-IV adverse events were hypertension and liver function test (LFT) abnormalities. Longitudinal quality of life analysis will be added at the time of presentation as well. Conclusions: Given that the primary endpoint was met, these data suggest that there is a benefit to front-line pazopanib in patients who are not candidates for cytotoxic chemotherapy. Clinical trial identification: NCT02300545. Legal entity responsible for the study: Washington University in St Louis. Funding: Novartis/GSK. Disclosure: M. Agulnik: Advisory / Consultancy: Novartis; Advisory / Consultancy: Lilly; Advisory / Consultancy: Immune Design; Advisory / Consultancy: Bayer; Speaker Bureau / Expert testimony: Janssen; Speaker Bureau / Expert testimony: Eisai; Speaker Bureau / Expert testimony: BMS; Speaker Bureau / Expert testimony: Bayer. M. Varun: Travel / Accommodation / Expenses: Deciphera; Research grant / Funding (institution): Immunocellular; Research grant / Funding (institution): Orbus Therapeutics. M. Milhem: Advisory / Consultancy: Amgen; Advisory / Consultancy: Trieza; Advisory / Consultancy: Biontech; Advisory / Consultancy: Blueprint medicine cooperation; Advisory / Consultancy: Immunocore; Advisory / Consultancy: Array BioPharma, Inc. S. Robinson: Research grant / Funding (institution): TRACON; Honoraria (institution), Advisory / Consultancy: BTG International; Honoraria (institution), Advisory / Consultancy: Society of Interventional Radiology Foundation. S. Attia: Research grant / Funding (institution): AB Science; Research grant / Funding (institution): TRACON Pharma; Research grant / Funding (institution): CytRX Corporation; Research grant / Funding (institution): Bayer; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Daiichi Sankyo; Research grant / Funding (institution): Lilly; Research grant / Funding (institution): Immune Design; Research grant / Funding (institution): Karyopharm Therapeutics; Research grant / Funding (institution): Epizyme; Research grant / Funding (institution): BluePrint Medicine; Research grant / Funding (institution): Genmab; Research grant / Funding (institution): CBA Pharma; Research grant / Funding (institution): Desmoid Tumor Research Foundation; Research grant / Funding (institution): Merck; Research grant / Funding (institution): Philogen; Research grant / Funding (institution): Laboratories; Research grant / Funding (institution): Bavarian Nordic; Research grant / Funding (institution): BTG; Research grant / Funding (institution): PTC Therapeutics; Research grant / Funding (institution): GlaxoSmithKline; Research grant / Funding (institution): FORMA Therapeutics. B.A. Van Tine: Advisory / Consultancy, Research grant / Funding (self), Travel / Accommodation / Expenses: Lilly; Research grant / Funding (institution): Merck; Research grant / Funding (institution): Tracon; Advisory / Consultancy: CytRX; Advisory / Consultancy, Speaker Bureau / Expert testimony: Janssen; Advisory / Consultancy: Immune Design; Advisory / Consultancy: Daiichi Sankyo; Advisory / Consultancy: Plexxicon; Advisory / Consultancy: Pfizer; Advisory / Consultancy, Speaker Bureau / Expert testimony: Adaptimmune; Speaker Bureau / Expert testimony: Caris; Advisory / Consultancy: Bayer. All other authors have declared no conflicts of interest.